The Effectiveness of Drug-Free ASEAN by 2015: Overcoming Drugs Trafficking in Indonesia - Asma Amin (Indonesia Prime, 2020)
This study aimed to explore the effectiveness of ASEAN cooperation implementation through the commitment of "Drug Free ASEAN 2015" in dealing with drugs trafficking in Indonesia. The study was conducted by using a qualitative approach. Data from this study was collected by using three methods: interview, document-based research, and internet-based research. The used data were between year 2000-2015. The result indicated that the implementation of the ASEAN free drug 2015, that has been out of dated, has not realized the maximum results in overcoming drugs trafficking in Indonesia, this seen in a work plan that does not work in targets, namely: a significant reduction in illegal cultivation, smuggling and drug trafficking and the prevalence of drug abuse. Until now Indonesia is still categorized as a drug emergency area. Factors affecting the effectiveness of Drug Free ASEAN 2015 include aggressive commitment; non-binding agreements; Indonesia faces a strong and various of international network, Indonesia's internal conditions that support the entry and development of drug abuse in Indonesia as well as the New Psychoactive Substances (NPS) entering Indonesia.